Correlation between viscoelastic behavior and morphology of nanocomposites based on SR/EPDM blends compatibilized by maleic anhydride. (24th March 2017) - Bazli, Leila; Khavandi, Alireza; Boutorabi, Mohammad Ali; Karrabi, Mohammad
Abstract: Silicone rubber (SR)/ethylene-propylene-diene monomer (EPDM)/nanoclay (Cloisite15 A) nanocomposites with various compositions were prepared via melt compounding using a two-roll mill. The maleic anhydride grafted ethylene-propylene-diene monomer (MAH-g-EPDM) was used as a compatibilizer in this immiscible system. The effect of adding the nanoclay and MAH-g-EPDM on the oscillatory shear rheological properties, dynamic mechanical performance, relaxation behavior and morphology of the nanocomposites were studied. Cole-Cole, Van Gurp-Palmen and Han plots revealed a good dispersion of the filler in EPDM and an agglomeration of it in SR, which were also presented in XRD analysis. Furthermore, it was observed that MAH can have a compatibilizing effect on the nanocomposites only in the presence of the nanoclay, which was in agreement with the DMTA results. Based on SEM observations, spherical and elongated droplet structures were observed for the rubber blends and nanocomposites, respectively. In addition, droplets in MAH and the nanoclay-containing samples were more regular than the MAH-free ones, which asserts the synergistic effect of these two components. Moreover, interfacial tensions between the matrix and dispersed phase calculated from the Palierne model provided a good insight for the obtained results. Graphical abstract: Highlights: The influence of the nanoclay and compatibilizer addition on the viscoelastic parameters and morphology was studied. The results of viscoelastic plots and the SEM photographs were correlated and were in a good agreement with the Palierne model. The torsion stress relaxation test, before and after curing showed interesting results confirmed by the viscoelastic plots. Generally, maleic anhydride enhanced the viscoelastic properties and morphology of the nanocomposites.